Shared Experience Workshop Report (Part II): Reflections on University and Community Research Partnerships - Allwork, Larissa (University of Nottingham, 2016)
On 19th September 2016, university and community participants in research projects funded by the Centre for Hidden Histories convened for a ‘Shared Experience Workshop’ at Derby Riverside Centre. The day was organised by Impact Fellow, Dr Larissa Allwork, Community Liaison Officer, Mike Noble and Centre for Hidden Histories, Principal Investigator, Professor John Beckett.